Angel De Cora, Karen Thronson, and the art of place : how two Midwestern women used art to negotiate migration and dispossession - Sutton, Elizabeth A. (Iowa and the Midwest experience., 2020)
"Angel De Cora (c. 1870-1919) was a Native Ho-Chunk artist who received relative acclaim during her lifetime. Karen Thronson (1850-1929), on the other hand, was a Norwegian settler housewife who created crafts and folk art in obscurity along with the other women of her small immigrant community. Tracing the parallel lives of these two women artists at the turn of the 20th century, art historian Elizabeth Sutton reveals how their stories intersected and diverged in the American Midwest. Sutton, the great-great-granddaughter of Thronson, never loses sight of how her European ancestors' paths to land ownership were inextricably linked to Native American dispossession. By examining the creations of these two artists, she shows how each woman produced art or handicrafts that linked her new home to her homeland. Although De Cora's movements were initially forced, she nonetheless found ways to preserve her cultural identity through her art, retaining connections to her homeland and the sacred beliefs of her people. Thronson, too, sought to stay connected to her Norwegian roots, even though she actively chose to emigrate. As Sutton discovers, both women had to navigate and negotiate between asserting their authentic self and the expectations placed on them by others in their new locations. The result is a fascinating story of two women that speaks to universal themes of Native displacement, settler conquest, and the connection between art and place. It should be of interest to Midwestern and American West historians, American women's studies scholars, and general Midwest readers, as well"--